CHARACTERIZATION OF Pongamia pinnata L.Pierre. A REVIEW - Rout, S.; Beura, S.; Nayak, S.; Patra, S.S. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Pongamia pinnata L.Pierre belongs to Leguminaceae family is underutilized tree. It’straditionally used as illuminating oil and for lubrication and as curing medicine. In thepresent study Pongamia pinnata was studied for its multipurpose uses as watershedafforestation, avenue plantation and ethnomedicinal information. Overall, this paper gives anoverview on covering the biology, and various industrial uses.